Acoustic properties of lightweight foamed concrete with eggshell waste as partial cement replacement material - Lim, Siong Kang; Foo, Kar Poh; Lee, Foo Wei; Tiong, Hock Yong; Lee, Yee Ling; Lim, Jee Hock; King, Yeong Jin (Penerbit Universiti Kebangsaan Malaysia, 2021)
Nowadays, almost every industry needs to undergo green and sustainable industrial revolution due to pollutions like waste dumping and noise that deteriorating the environment. Therefore, feasibility study on application of eggshell waste as partial cement replacement in lightweight foamed concrete was conducted by aiming to solve environmental and acoustical issues, i.e. reduce eggshell waste and improve acoustic properties. In this study, compressive strength and acoustic properties of 1300 kg m-3 lightweight foamed concrete with and without 5% eggshell powder as partial cement replacement material were tested. Optimal water to cement ratio of 0.6 was obtained for acoustic properties test by comparing compressive strength result. The result shows that application eggshell powder has generally reduced 7 days compressive strength but improved 28 days compressive strength, and either improve or maintain acoustics properties, in which lightweight foamed concrete that containing eggshell powder has improved noise reduction coefficient at testing ages of 7, 28, and 90 days and improved sound transmission class at testing age of 56 and 90 days. Based on these results, 5% of eggshell powder is feasible to be incorporated into lightweight foamed concrete as partial cement replacement material for sound insulation and strength development purposes.